PENGARUH KOMPLEKSITAS TUGAS DAN INDEPENDENSI TERHDAP KUALITAS AUDIT DENGAN INTEGRITAS AUDITOR SEBAGAI VARIABEL MODERASI (Studi Pada Auditor di KAP di Jawa Tengah dan DIY) - Akbar Wiba Erlandi, 14.05.52.0190; Himmawan, Arief (Students' Journal of Accounting and Banking, 2018)
Audit quality is the quality of an auditor's work which is shown by a reliable audit report. Audit quality is influenced by various factors including task complexity, independence and auditor integrity. This study aims to examine the effect of task complexity and independence on audit quality with auditor integrity as a moderating variable. The population in this study were all auditors working in the Public Accounting Firm in Central Java and Yogyakarta Special Region (DIY). Sampling was carried out using convenience sampling method and obtained a sample of 73 respondents. Primary data collection methods are carried out through a survey method using a questionnaire. The data obtained were analyzed using multiple linear regression models and used a residual test to examine the effect of the moderating variable through SPSS 21.0. The results of this study indicate that the complexity of the task does not affect audit quality. Independence has a positive effect on audit quality, and Integrity Auditors do not moderate the influence of task complexity and independence on audit quality. Keywords: task complexity, independence, auditor integrity and audit quality.